2022
DOI: 10.1002/agm2.12216
|View full text |Cite
|
Sign up to set email alerts
|

A consolidated review on stem cell therapy for treatment and management of Alzheimer's disease

Abstract: Memory loss, emotional fluctuations, and functioning impairments are frequent signs of Alzheimer's disease (AD). Dementia, which includes AD, affects 50 million people worldwide, the majority of whom are elderly. AD is the world's fifth biggest cause of mortality, according to the World Health Organization (WHO), with the number of fatalities expected to quadruple by 2050 if present trend continue. 1,2 Brain imaging, physical and cognitive examinations, laboratory testing, and medical history are used to diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Therefore, it has been confirmed in numerous studies that depression as a neurodegenerative disorder resulting in atrophy of the brain regions 21 . Neurodegenerative disorders develop due to loss of neurons, resulting in a decline in cognitive functioning of the brain 22–28 . Several studies have identified the hippocampus as the key brain region linked to depression, and hippocampal plasticity occurs in patients with depression 29 .…”
Section: Overview On Depressionmentioning
confidence: 96%
“…Therefore, it has been confirmed in numerous studies that depression as a neurodegenerative disorder resulting in atrophy of the brain regions 21 . Neurodegenerative disorders develop due to loss of neurons, resulting in a decline in cognitive functioning of the brain 22–28 . Several studies have identified the hippocampus as the key brain region linked to depression, and hippocampal plasticity occurs in patients with depression 29 .…”
Section: Overview On Depressionmentioning
confidence: 96%
“…MSCs are a diverse kind of stromal stem cell that can be separated from a variety of adult tissues [ 75 , 76 ], such as the umbilical cord, endometrial polyps, bone marrow, adipose tissue, and others [ 77 ]. They can segregate into mesodermal lineage cells such as osteocytes, adipocytes, chondrocytes, and some other embryonic lineages [ 75 ].…”
Section: Mesenchymal Stem Cells and Depression: A Therapeutic Mechanismmentioning
confidence: 99%
“…The long-term survival of transplanted neural cells into the brain has been prolonged by immunosuppression of xenograft rejection in AD model mice [124]. Currently, many stem cell therapies have progressed well in clinical trials [33,125] by accumulating findings through basic research, including animal experiments. Therefore, stem cell therapy is a promising future clinical application.…”
Section: Conclusion 11mentioning
confidence: 99%
“…The discovery of induced pluripotent stem cells (iPS cells) has enhanced the development of regenerative medicine for neurodegenerative diseases, such as Parkinson's disease [27,28], spinal cord injury [29][30][31], hemiplegia [32], and AD [33].…”
Section: Introductionmentioning
confidence: 99%